MARXISME DAN BURUH INDONESIA KONTEMPORER: STUDI DIMENSI RELEVANSI DAN INRELEVANSI PEMIKIRAN SOSIAL-EKONOMI KARL MARX PADA BURUH PABRIK DI KOTA SURABAYA - Wijaya, Yoseph Fredy; Nugroho, Wahyu Budi; Punia, I Nengah (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
This research aims to deepen comprehension about Marxism, especially social and economic thought of Karl Marx. Karl Marx was a thinker who has a lot of influence on the development of the community. Social and economic thought of Karl Marx further analyzed to find out the dimensions of relevance and inrelevance in the life of contemporary laborers. In his study Marx put forward related alienation inherent in the life of the labourers who were born by the system of capitalism. This research is a joint research literature study and field study. Data in this research is text related to Marxism and field data through interviews with workers as informant. As for the results of this research found that first,Karl Marx social thought includes the alienation of labor on the resulting products, labour alienation of work activities, alienationlabour over their fellow workers, and religious alienation;Marxeconomic thought includes alienation of value for use, surplus value, commodity fetishism, and capital circulation. Secondly, based on field analysis found that Karl Marx thought still has relevance to the life of laborers in the city of Surabaya. Nevertheless, some of Marx's ideas which no longer find relevance include Marx's predictions of labor poverty and the collapse of capitalism because of the movement of laborers. Keywords: Marxism, Karl Marx, alienation, labor.